A Near‐Infrared Emissive π‐Conjugated Polymer Consisting of an Excited‐State Intramolecular Proton Transfer Unit. Issue 9 (23rd July 2020) - Suzuki, Naoya; Wakioka, Masayuki; Ozawa, Fumiyuki; Yamaguchi, Shigehiro
Abstract: Near infrared (NIR)‐emissive polymers are attractive luminescent materials due to their utilities in biological, optoelectronic, and telecommunication applications. Herein we report the use of a dialkylamine‐strapped dithienylpyrrole (DTP) as an excited‐state intramolecular proton transfer (ESIPT) building block for producing NIR‐emissive π‐conjugated polymers. The study of a series of model compounds showed that the extension of π‐conjugation with a moderately electron‐accepting comonomer unit, dithientyl‐substituted thiazolo[5, 4‐d]thiazole (TzTz), effectively stabilizes the zwitterionic ESIPT state while increasing the oscillator strength for the electronic transition from the ESIPT state. Consequently, a polymer consisted of DTP and TzTz units exhibited a significantly red‐shifted emission, exceeding 750 nm, from the ESIPT state in polar solvents. Abstract : Upon excitation, dialkylamine‐strapped dithienylpyrrole undergoes the excited‐state intramolecular proton transfer (ESIPT), resulting in enhancement of the electron‐donating ability. An alternating polymer of this skeleton with an electron‐accepting thiazolo[5, 4‐ d ]thiazole unit retains the ESIPT behavior, and exhibits a NIR emission with a large Stokes shift in polar solvents.